Calophyllum brasiliense Modulates the Immune Response and Promotes Leishmania amazonensis Intracellular Death - L. Domeneghetti; I. G. Demarchi; J. Z. Caitano; R. B. Pedroso; T. G. V. Silveira; M. V. C. Lonardoni (Mediators of Inflammation)
Calophyllum brasiliense is a plant from the Brazilian rain forests and has been used in folk medicine for the treatment of various diseases, including leishmaniasis. This infectious disease depends on the Leishmania sp. and the host immune response. C. brasiliense antileishmanial activity is well known, but the effects on immune response remain to be investigated. This study showed the leishmanicidal and immunomodulatory effects of a 30 μg/mL of hydroalcoholic extract of C. brasiliense in murine macrophages before and after Leishmania (Leishmania) amazonensis infection. The semiquantitative cytokine RNA expression was determined by RT-PCR and the anti-Leishmania activity was measured by infection index (IF). Hydroalcoholic extract of C. brasiliense reduced more than 95% of IF when used before and after Leishmania infection, with 3 and 24 h of treatment (p<0.05). C. brasiliense inhibited or reduced significantly (p<0.05) the TNF-α, IL-1β, IL-18, and IL-10 mRNA expression. The antileishmanial and anti-inflammatory effects showed the potential of C. brasiliense as an alternative therapy for leishmaniasis and it must be investigated.